Comparative analysis of ceramic flexural strength in co-cr and ni-cr alloys joined by TIG welding and conventional brazing - Adaias Oliveira Matos; Cristiane de Castro Castelo Branco; Eliza Burlamaqui Klautau; Bruno Pereira Alves (Universidade Estadual de Campinas, 2017)
The purpose of the present study was to evaluate the flexural strength of specimens made of nickel-chromium (Ni-Cr) and cobalt-chromium (Co-Cr) alloys and joined by tungsten inert gas (TIG) welding and conventional brazing. Ni-Cr and Co-Cr base metal specimens (n = 40, each) were cast and welded by TIG or brazing. The specimens were divided into six groups (2 base metals, four welded specimens). Ceramic systems were applied to the central part of all the specimens. A three-point bending test with a velocity of 0.5 mm/m was performed on the specimens up to the point of the first ceramic bond failure by measuring the flexural strength. Data were analyzed using two-way ANOVA and Bonferroni's tests. Conventional welding showed the lowest flexural strength results for both alloys, while the TIG weld and the control group presented with varying bond strengths for the alloys studied. We concluded that TIG welding was superior to the conventional welding method for both Ni-Cr and Co-Cr alloys with regard to the flexural strength of the ceramic.